Analysis of Learning Quality With Internet-Based Distance Learning During the COVID-19 Pandemic - Yuli Sutoto Nugroho; Lilik Anifah; Edy Sulistiyo; Sari Cahyaningtias; Rifqi Firmansyah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Analysis of the quality of learning is crucial in the teaching and learning process, to ensure the quality of learning is well maintained. Learning quality assurance instruments are one of the tools to improve quality in education through evaluations produced by studies of students. This research was conducted to test the quality of online learning during the COVID-19 pandemic. This research aims to evaluate Internet-Based Distance Learning which was carried out during the Work From Home (WFH) period. The learning analysis step is carried out through 1) Formulation of the need for quality analysis of learning, 2) Compiling quality analysis instruments, 3) Distribution of questionnaires, 4) Data processing, 5) Data analysis and 6) Compilation of results. The data analysis technique used descriptive qualitative analysis. The data that has been processed will then be analyzed using descriptive qualitative methods to find conclusions about the quality of learning in the Department of Electrical Engineering (JTE) during the 2020 pandemic. From the analysis, results obtained information that the Quality of Learning with Internet-Based Distance Learning during the COVID-19 Pandemic at JTE it can be said that it is good from a student's point of view, while from a lecturer's point of view, It can be concluded that online learning is very good. The implementation of this research is a consideration for JTE to improve the quality of Internet-Based Distance Learning